Therapeutic Effects of Manual Therapy on Lateral Epicondylitis: A Randomised Controlled Trial - Rachold, Wolfgang; Reis, Olaf; Berger, Christoph; Buchmann, Johannes (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2022)
Background Epicondylopathia humeri radialis is often diagnosed by general practitioners. Usually, the therapy comprises transcutaneous electrical nerve stimulation using a forearm brace. Manual therapy, performed by specialised physiotherapists, is prescribed before transcutaneous electrical nerve stimulation and forearm brace use. However, studies comparing the effectiveness of all methods are scarce.Objective To compare the therapeutic effects of manual therapy, transcutaneous electrical nerve stimulation, and forearm brace use, as well as the combination of all three.Methods Fifty-two patients diagnosed with epicondylopathia humeri radialis were randomised into three treatment arms: a combination of manual therapy, transcutaneous nerve stimulation, and forearm brace use (n=19); manual therapy only (n=18); and a combination of forearm brace use and transcutaneous nerve stimulation (n=15). All measurements and therapies, excluding manual therapy, were performed at the first author’s practice premises. The primary outcomes included range of motion and pain intensity; the secondary outcomes were elbow function and psychological well-being. Primary and secondary outcomes were measured before and at 4 and 8 weeks after treatment using the Patient Rated Tennis Elbow Evaluation Questionnaire and the Short Form Health Survey Questionnaire.Results The range of motion and pain intensity did not differ among the groups.Conclusion Manual therapy alone was as effective as the combination of transcutaneous nerve stimulation and forearm brace use for epicondylopathia humeri radialis. Our findings support the inclusion of manual therapy as a stand-alone therapy option in the guidelines for treating patients with epicondylopathia humeri radialis.
Keywords: Musculoskeletal Manipulations; Tennis Elbow; Trigger Points; Elbow Joint; General Practice; Tendinopathy